Implementation of the Balanced Score Card to Achieve Strategic Goals in the State Islamic Religious Colleges - Yusuf Hadijaya; Inom Nasution; Suhairi Suhairi (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2019)
Performance Management in State Islamic Religious Colleges (PTKIN) Indonesia are still often ignoring the identification of stakeholders and the primary performance indicator of management measurement goal. The Balanced Score Card (BSC) as a management approach translates the direction of Higher Education developing into an action based on the initiatives identity number and management measurement goal systems. In the context aims to determine the implementation of the Balanced Score Card at PTKIN with four perspectives which are connected as part of the chain driving to achieve the strategic point of Higher Education and performance of higher education results model. This research is qualitative research with the technique of data collection on observation, in-depth interviews, and documentation. The results paper shows that the Balanced Score Card is the performance integrating on management system at UIN Jakarta, UIN Yogyakarta, and UIN North Sumatera through the making of Score Cards with the processing of strategy maps to achieve its strategic point of higher education objectives. The Map Strategy is preparing as a companion model for its BSC implementation management goal of Higher Education. Keywords: Balanced Scorecard, Strategic Objectives, Initiatives, and Performance Indicators Abstrak Manajemen Kinerja di banyak Perguruan Tinggi Keagamaan Islam Negeri (PTKIN) di Indonesia masih sering mengabaikan identifikasi stakeholders dan sistem pengukuran indikator kinerja utama. Balanced Score Card (BSC) sebagai sebuah pendekatan manajemen menerjemahkan arah pengembangan Perguruan Tinggi pada aksi yang dilandasi oleh identifikasi inisiatif dan sistem pengukuran. Dalam konteks ini, penelitian ini bertujuan untuk mengetahui implementasi Balanced Score Card di PTKIN dalam empat perspektif yang dihubungkan sebagai bagian dari rantai pendorong untuk mencapai tujuan-tujuan strategis dan hasil capaian kinerja. Penelitian ini merupakan penelitian kualitatif dengan teknik pengumpulan berupa observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa BSC diintegrasikan dalam sistem manajemen kinerja di UIN Jakarta, UIN Yogyakarta, dan UIN Sumatera Utara melalui pembuatan score cards dan/atau peta strategi dalam mencapai tujuan-tujuan strategis. Kata Kunci: Balanced Score Card, Tujuan Strategies, Inisiatif, dan Indikator Kinerja